Restoring the Extracellular Matrix: A Neuroprotective Role for Collagen Mimetic Peptides in Experimental Glaucoma - McGrady, Nolan R.; Pasini, Silvia; Baratta, Robert O.; Del Buono, Brian J.; Schlumpf, Eric; Calkins, David J. (Frontiers in Pharmacology, 2021)
Optic neuropathies are a major cause of visual disabilities worldwide, causing irreversible vision loss through the degeneration of retinal ganglion cell (RGC) axons, which comprise the optic nerve. Chief among these is glaucoma, in which sensitivity to intraocular pressure (IOP) leads to RGC axon dysfunction followed by outright degeneration of the optic projection. Current treatments focus entirely on lowering IOP through topical hypotensive drugs, surgery to facilitate aqueous fluid outflow, or both. Despite this investment in time and resources, many patients continue to lose vision, underscoring the need for new therapeutics that target neurodegeneration directly. One element of progression in glaucoma involves matrix metalloproteinase (MMP) degradation of the collagen-rich extracellular milieu of RGC axons as they exit the retina through the optic nerve head. Thus, we investigated the ability of collagen mimetic peptides (CMPs) representing various single strand fractions of triple helix human type I collagen to protect RGC axons in an inducible model of glaucoma. First, using dorsal root ganglia maintained in vitro on human type I collagen, we found that multiple CMPs significantly promote neurite outgrowth (+35%) compared to vehicle following MMP-induced fragmentation of the α1(I) and α2(I) chains. We then applied CMP to adult mouse eyes in vivo following microbead occlusion to elevate IOP and determined its influence on anterograde axon transport to the superior colliculus, the primary RGC projection target in rodents. In glaucoma models, sensitivity to IOP causes early degradation in axon function, including anterograde transport from retina to central brain targets. We found that CMP treatment rescued anterograde transport following a three-week +50% elevation in IOP. These results suggest that CMPs generally may represent a novel therapeutic to supplement existing treatments or as a neuroprotective option for patients who do not respond to IOP-lowering regimens.